Fixing and flipping real estate : strategies for the post-boom era - Boardman, Marty (Apress Imprint: Apress, 2013)
Let's face it-fixing and flipping houses is sexy. Who doesn't love the idea of buying a rundown, mold-infested shack and transforming it into someone's dream home for massive profits? Reality TV shows make it look so easy. A little paint here, some new kitchen cabinets there, and presto! The house is sold for big bucks and everyone lives happily ever after. If only it were that simple. Fixing and flipping houses is a business. In order for a business to survive, prosper, and grow, systems must be put in place. Fixing and Flipping Real Estate: Strategies for the Post-Boom Era is a book that breaks down the four essential components of a fix-and-flip business, giving you the building blocks to efficiently buy and sell 1 to 20 properties a month in today's post-boom era housing market. You'll learn about each of the boxes: Acquisition-How to find and buy a profitable real estate deal. Rehabbing-How to systematically remodel a house and how not to underimprove, or overimprove, your property. Sales-How to sell your flip for the highest possible price in the shortest possible time. Raising Capital-How to get the capital you need to grow your business, including using other people's money, for your real estate deals without getting sued or going to jail. In the post-real estate boom era, fixing and flipping is again a solid business--especially in the "sand" states-Arizona, California, Nevada, Texas, and Florida, among others. It's also a good bet in states as diverse as North Carolina and Washington State. And with the real estate market projected to bottom out nationally in 2012 (this time for real), there are plenty of houses to be renovated and plenty of money to be made by the enterprising in all fifty states. This book shows real estate investors everything they need to know to get started fixing and reselling houses either as a substantial sideline or a full-on business.